2021
DOI: 10.1002/hep.32265
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hepatitis B vaccination in the United States, 1999–2018

Abstract: Background and Aims Hepatitis B vaccine has been included in the infant immunization schedule since 1991 in the United States. We aimed to assess its effectiveness against HBV infection and its impact on mortality. Approach and Results The study population was participants aged 6+ years with an HBV vaccination history and an HBV serologic test from the National Health and Nutrition Examination Survey, 1999–2018. Participants aged 18+ years with linked mortality records from 1999–2014 were followed for mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In general, a 70% to 94% effectiveness range has been reported, depending mainly on the follow-up time, the exposure risk rate (HBsAg prevalence of the population), and the studied cohort age[ 18 , 23 , 55 ]. A recent study showed an approximately 58% effectiveness in a birth cohort (mean age, 12 years) and 85% in participants at least 20-years-old[ 56 ]. The lower efficacy observed in the birth cohort could be a consequence of a lower level of exposure.…”
Section: Immunitymentioning
confidence: 99%
“…In general, a 70% to 94% effectiveness range has been reported, depending mainly on the follow-up time, the exposure risk rate (HBsAg prevalence of the population), and the studied cohort age[ 18 , 23 , 55 ]. A recent study showed an approximately 58% effectiveness in a birth cohort (mean age, 12 years) and 85% in participants at least 20-years-old[ 56 ]. The lower efficacy observed in the birth cohort could be a consequence of a lower level of exposure.…”
Section: Immunitymentioning
confidence: 99%
“…Another 14 countries showed a consistent reduction of primary liver cancer mortality in the most recent 10 years from both WHO and GBD study, including Japan, Kazakhstan, Peru, Slovakia, South Africa. Most to these countries have high burden of HBV infections in the past, but because of the success of universal HBV vaccination programme as well as the introduction of HCV screening and administration of effective antiviral treatment for HBV and HCV 24–26 …”
Section: Discussionmentioning
confidence: 99%
“…Most to these countries have high burden of HBV infections in the past, but because of the success of universal HBV vaccination programme as well as the introduction of HCV screening and administration of effective antiviral treatment for HBV and HCV. [24][25][26] Of significance, opposite trends in five countries from South America, four countries in Europe and one country in Asia between the WHO and GBD data raised concerns of the actual patterns of liver cancer mortality from these countries. For seven of these ten countries, the estimates from WHO suggested a reduction of primary liver cancer mortality in the last 10 years while substantial increase was found from GBD in the same period.…”
mentioning
confidence: 99%
“…Prevention of hepatitis-induced HCC occurs through prevention of exposure, inoculation with the hepatitis B vaccine (currently there is no hepatitis C vaccine), and/or treatment with targeted antiviral medications [ 5 ]. The expansion of vaccine inoculation in the United States, which was incorporated into the infant inoculation schedule in 1991, has greatly reduced the risk of hepatitis and cancer related mortality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%